Activation, proliferation, and differentiation of progenitor cells into hepatocytes in the D-galactosamine model of liver regeneration. - Dabeva, M. D. (1993)
Rat liver regeneration was studied from 24 hours to 8 days after a single intraperitoneal injection of D-galactosamine (GalN). Morphological changes in the liver were analyzed in parallel with sequential changes in expression of histone-3 mRNA (a marker of cell proliferation), fetal alpha-fetoprotein (AFP) mRNA and gamma-glutamyl transpeptidase (GGT) (markers of fetal hepatocytes), and albumin mRNA and glucose-6-phosphatase (G6Pase) (markers of adult hepatocytes). Proliferation of nonparenchymal epithelial cells (NPC), detected in situ by [3H]thymidine labeling or histone-3 mRNA expression, began after 24 hours primarily in the portal area around the bile ducts. After 2 days, histone-3 labelling intensity increased in rows and clusters of NPC which expanded from the portal zone and invaded into the parenchyma. On days 3 and 5, NPC expressing his-3 mRNA expanded further, forming pseudo-ducts and islet-like structures (NPC structures). Proliferating NPC were positive for GGT. Some GGT positive cells were also positive for the fetal form of AFP mRNA, which lagged behind GGT by 24 hours and peaked on day 5. On day 3, some cells with the appearance of NPC expressed albumin mRNA. Double label in situ hybridization for fetal AFP and albumin mRNAs and dual histochemistry for GGT and G6Pase showed simultaneous expression of these markers in NPC on day 5. Other cells expressing fetal AFP mRNA or GGT on day 5 had a morphological appearance between NPC and hepatocytes (transitional cells). Proliferation of hepatocytes began on day 2, reached maximum on day 5 and then declined. Proliferating hepatocytes did not express fetal AFP mRNA or GGT. These findings indicate that after GalN injury, the liver responds by activation of progenitor cells that proliferate and then differentiate into mature hepatocytes. Adult hepatocytes can also proliferate after GAlN injury, but these hepatocytes do not undergo dedifferentiation/redifferentiation during regeneration of the hepatic lobule.